Viability template – a practical tool for assessing viability of transformative service innovations in health care context - Kaartemo Valtteri; Heikkilä Marikka; Saarni Jouni; Koponen Aki (Finland, 2022)
The paper develops and showcases the viability template which is designed to assess the innovation potential of transformative service ideas. Based on the transformative service research and innovation literature, we highlight the importance of novel simplifying technology, supporting value networks, cost-effective business models, and regulatory environment which enable renewal of the prevailing market practices. We operationalize the template as a set of questions and assess the innovation potential of three pilot cases on new transformative services. The pilot cases present technologies that aim to develop and spread the usage of user-friendly electronic health care services in Finland.
Proceedings of XXIV Annual RESER Conference 2014